Komunikasi Politik dalam Perombakan Kabinet Bersatu Jilid Dua - Sukarno, Bedjo (Transformasi, 2012)
AbstractPoor performance of most government ministries result in a decline in public confidence, a reflection in the form of criticism and public opinion as a government policy of political communication that are not able to meet community expectations. Policies decided by the government in a cabinet reshuffle united volume two is a fundamental government reform measures, thorough, consistent, clear agenda to improve the political order, and justice in the rule of law.Key word: Performance, Political Communication, Reshuffle